Competência no desenvolvimento de novos serviços (DNS) no setor de serviços de valor agregado (SVA) no segmento de telefonia móvel - Santos, Tânia Letícia dos (2014)
Constant technological advances and the increasing popularity of mobile devices among mobile phone users is strongly impacting the sector of Value Added Services. In this context, the continuing development of new products and services is critical for competitive survival of Value Added Services organizations. The objective of this study is to understand the relationship between competence in new services development of (NSD) and the innovative performance of new services development. In the conceptual approach of this study a multidimensional view of competence that encompasses the dimensions of competence in the practice of NSD and the organizational context was adopted, and the innovative performance based on the frequency of the different innovation types and grades of DNS program . The specific objectives of this study are: i) identify the individual and collective competence by competence in the practice of NSD, which comprises competence in NSD, in terms of NSD staff, sources of knowledge for NSD, NSD process and use of Information Technology; ii) identify the organizational competence through the organizational context, which comprises competence in NSD, in terms of innovation culture, NSD policies and NSD resources; iii) identify the innovative performance of NSD in terms of frequency of the different innovation types and grades of DNS program ; iv) identify the relationship between NSD competence and NSD innovative performance. The choice to meet the objectives of this study approach is quantitative type of survey, using the technique of structural equation modeling - based variance estimation via partial least squares (PLS). The analysis of the measurement and structural model showed that competence in NSD construct , comprised by competence in the practice of NSD and organizational context dimensions, has positive and strong effect relationship with the NSD innovative performance construct, the latter especially determined by incremental innovation.